Development of a coastal dune vulnerability index for Mediterranean ecosystems: A useful tool for coastal managers?. (5th March 2017) - Ciccarelli, D.; Pinna, M.S.; Alquini, F.; Cogoni, D.; Ruocco, M.; Bacchetta, G.; Sarti, G.; Fenu, G.
Abstract: Coastal dune ecosystems have been severely degraded as a result of excessive natural resource exploitation, urbanisation, industrial growth, and worldwide tourism. Coastal management often requires the use of vulnerability indices to facilitate the decision-making process. The main objective of this study was to develop a Mediterranean dune vulnerability index (MDVI) for sandy coasts, starting from the existing dune vulnerability index (DVI) proposed by Garcia-Mora et al. (2001) related to the oceanic coasts. Given that the Mediterranean sandy coasts are quite different from the Atlantic coasts, several adjustments and integrations were introduced. Our proposed index is based on the following five main group of factors: geomorphological conditions of the dune systems (GCD), marine influence (MI), aeolian effect (AE), vegetation condition (VC), and human effect (HE), for a total of 51 variables derived (and adapted) from the bibliography or proposed for the first time in this study. For each coastal site, a total vulnerability index, ranging from 0 (very low vulnerability) to 1 (very high vulnerability), was calculated as the unweighted average of the five partial vulnerability indices. Index computation was applied to 23 coastal dune systems of two different contexts in Italy, i.e. peninsular and continental island territories representative of the W-Mediterranean Basin, in order to compare the dune systems with different geomorphology, shoreline dynamics, and human pressure. In particular, our research addressed the following two questions: (1) Which variables are the most critical for the Italian coastal systems? (2) How can the coastal dune vulnerability index be used to develop appropriate strategies of conservation and management for these ecosystems? Cluster analysis and non-metric multidimensional scaling separated the peninsular from the insular sites, both of which were characterised by low to moderate values of vulnerability (0.32 < MDVI < 0.49). The most critical factors for the coastal systems examined in this study were marine negative influence, low stabilising ability of vegetation, and human disturbance. Hence, coastal managers are encouraged to plan specific management actions such as protection of foredunes from marine factors (particularly erosion), to promote dune formation with the reintroduction of native dune builder species and to minimise human pressure where vulnerability depends on these variables. Highlights: Vulnerability indices are useful for coastal management. A coastal dune vulnerability index for Mediterranean coasts (MDVI) was developed. Mediterranean coasts considered were characterised by low to moderate vulnerability. Marine influence, vegetation and human disturbance were the most critical factors. Managers are encouraged to protect dunes from erosion and minimise human pressure.